Microbiota fúngica de um prédio com laboratórios da região de Araraquara-SP - Martins-Diniz, J. N.; Silva, R. A. M. [UNESP]; Miranda, E. T. [UNESP]; Mendes-Giannini, Maria José Soares [UNESP] (My University, 2004)
From September 2000 to January 2001, airborne fungi were isolated from the building of the Clinical Analyses laboratories, including its didactic and research rooms, in Araraquara São Paulo State, Brazil, by using Andersen, MAS-100® (MERCK) machine, with Sabouraud chloramphenicol medium. After 5 days of incubation at 25°C, the colonies of the fungi were counted, resulting in the identification of 21 taxa. Cladophialophora spp. was the most isolated in internal and external environments as well, followed by Penicillium spp. and Mycelia spp. In accordance with the resolution n° 9, January 2003 (ANVISA), fungi considered unacceptable were found in nine internal environments and one of these presented the amount of fungi above of the acceptable limit. Among the obtained fungi, at least 16 taxa were reported as opportunistic, nine were related to plant diseases and seven were associated to allergy problems.
Environment fungi of laboratory buildings in Araraquara - SP region
Keywords: Airborne fungi; Bioaerosol; Microorganisms; chloramphenicol; airborne particle; allergy; cladophialophora; controlled study; disease association; fungal colonization; fungal strain; fungus culture; fungus identification; fungus isolation; incubation time; laboratory automation; mycelium; nonhuman; opportunistic infection; Penicillium; taxon